Experiences of community reintegration after obstetric fistula repair at Jean Paul 2 hospital, Conakry, Guinea. - Hady Kaba; Momo Aboubacar Touré; Mandian Camara; Mira Johri (Public Library of Science (PLoS), 2024)
The study explored women's experiences of their community reintegration process after surgical repair of obstetric fistula at Jean Paul 2 Hospital in Conakry, Guinea. The study examined how lived experiences of the disease impacted on the community reintegration of treated women. Using a qualitative research methodology, ten women participated after giving informed consent. Semi- structured interviews, lasting an average of 30 to 60 minutes were guided by an interview guide. The main themes covered were experiences with the disease, perceived social support and reintegration into the community. According to the participants, delays in obstetric care were the main cause of obstetric fistula. Socio- economic, cultural and medical factors such as early marriage, lack of education and poverty contributed to these delays. Even after surgical repair, women continued to endure the physical and psychosocial consequences of the disease, exposing them to stigma, discrimination and even rejection within the community. Study participants also reported a lack of social support. The little support perceived by these women concerned food and medical needs. This made the women dependent on their families. Reintegration into the community also proved difficult due to the persistent silence and stigma surrounding their situation. The study results highlight the complexity of the challenges faced by women with obstetric fistula in their journey towards integration. Effective management of obstetric fistula requires a holistic approach victims, their communities, health professionals and decision-makers in solving this problem. So, to improve women's reintegration after treatment for obstetric fistula, it is vital to raise awareness of the causes and consequences of the disease among the women concerned and their families, and to provide rapid access to emergency obstetric care, reinforce social support and set up economic empowerment programs.